Circularly Polarized Dual Band Dual Slot Antenna for WLAN, Wi-MAX and Wi-Fi Applications. Issue 3 (3rd April 2023) - Sura, Penchala Reddy; Sekhar, M.
Abstract : In the last 15 years, the growth in the modern wireless communication systems has motivated enlarged exploration on inexpensive circularly polarized dual band slot antennas. A simple circularly polarized dual band dual slot antenna for WLAN, Wi-MAX and Wi-Fi applications is designed and analyzed. The proposed CP dual band antenna contains a radiating rectangular patch with two slots on low cost FR4-substrate having thickness of 1.6 mm. The CP dual band antenna is capable of resonating between 3.35 to 3.9 GHz and 4.8 to 6 GHz with S11 below −11 dB value. The proposed antenna exhibits the axial ratio value less than 3 dB in the two bands. This antenna utilizes single offset microstrip line feed and does not require any complicated phase shift network to provide 90° excitation phase difference. Hence this antenna can be used to form larger arrays to achieve higher gain. The antenna performance is significantly affected by the dimensions of the slots. The projected antenna is optimized using the ansoft HFSS. The antenna is fabricated to test the performance. The antenna exhibits adequate gain at the two bands. There is reasonable agreement between the simulated results and measured values.